Photovoicing interconnected sources of recovery capital of women with a drug use history. (3rd September 2021) - Van Steenberghe, Tijs; Vanderplasschen, Wouter; Bellaert, Lore; De Maeyer, Jessica
Abstract: The voices of women in recovery have long been absent in treatment studies and addiction recovery debates. Available qualitative research primarily applies interview and focus group methods, but in this study we used an innovative photovoice method to uncover the personal recovery stories and pathways of women with a history of (illicit) substance use problems. Eight women who are initiating or maintaining recovery met monthly over a six-month period to select pictures and to share and find common themes, related to facilitators and barriers in their recovery process. The results highlight the complexities and positive and negative dynamics of recovery capital in relation to gender and other social constructs. Four themes were identified as building stones for initiating and maintaining recovery: (1) (Re-)building me; (2) Untangling what is life and what is addiction; (3) Becoming (re-)connected; and (4) (Enacting) perspectives on the future. The study revealed the methodological potential of the photovoice method for exploring interconnected recovery challenges among women, as well as the destructive impact of negative social norms on women's recovery experiences.